Food Crop Land Allocation: Integrating Land Suitability Analysis and Spatial Forestry, Study Case Katingan, Indonesia - Ramdhani; Widiatmaka; Trisasongko, Bambang Hendro (Jurnal Manajemen Hutan Tropika, 2023)
The Indonesian government strives to expand agricultural lands, primarily beyond Java, through food estate programs. However, there has been a strong likelihood that this endeavor might intersect with forests and forest designation areas. This study aims to determine land suitability and its potential allocation for food crops at the interface of forestry and agriculture in Katingan District. Paddy (Oryza sativa L) and sorghum (Sorghum bicolor L) were selected as the crop species being analyzed, employing a coupling of the analytical hierarchy process and GIS. Forest area designation and land cover maps were incorporated into land allocation scenarios. The results showed that there were 74.254 ha in the "highly suitable" (S1) class and 130.634 ha in the "moderately suitable" (S2) class for paddy. However, after applying the scenario, they decreased by 4% and 12%, respectively. Sorghum has S1 and S2 areas of 108.956 ha and 377.493 ha, which declined by 15% and 14%, respectively, after scenario. Based on the allocation scenario, we found potential deforestation of 67 thousand ha for paddy and 205 thousand ha for sorghum, respectively. We highlighted convertible production forests (HPK) and production forests (HP) as having considerable potential for the allocation of land for food production.